The Effect of Motivation, Organizational Culture and Discipline on Employee Performance: The Case of Islamic School at Bina Ilmi Palembang City - Saputra, Fadli; Asiati, Diah Isnaini; Choiriyah, Choiriyah (Training & Research Institute - Jeramba Ilmu Sukses, 2025)
This study aims to determine 1) The Influence of Motivation, Organizational Culture, and Work Discipline on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City, 2) The Influence of Motivation on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City, 3) The Influence of Organizational Culture on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City, 4) The Influence of Work Discipline on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City. This type of research is Associative. The variables used by the researcher include motivation, organizational culture, work discipline, and teacher performance. The sample in this study consisted of teachers at Bina Ilmi Integrated Islamic School, Palembang City, totaling 100 respondents selected by Cluster Sampling. The data used in this study were primary data collected using a questionnaire. The data analysis technique used was multiple linear regression. The results of this study indicate that (1) motivation, organizational culture, and work discipline together have a positive and significant effect on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City, (2) motivation has a positive and significant effect on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City (3) organizational culture has a positive and significant effect on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City (4) work discipline has a positive and significant effect on Teacher Performance at Bina Ilmi Integrated Islamic School, Palembang City.